A Change of Heart: Case Series of Peripartum Cardiomyopathy. (22nd December 2013) - Martin, Sean; Short, Daniel; Wong, Chih Mun; McLellan, Dina
Abstract : Peripartum cardiomyopathy (PPCM) is an uncommon disease of pregnancy, occurring in about 1 in 2000 live births, and is characterized by the development of heart failure, due to left ventricular systolic dysfunction. It is associated with high rates of maternal and neonatal mortality. Cardiac disease is the leading cause of maternal death in the UK: PPCM accounts for about 17% of these. Clinical findings of decompensated heart failure (HF) are often masked by the normal physiological changes seen in pregnancy making the diagnosis challenging. A high index of suspicion is essential—prompting referral for echocardiogram, which is crucial for diagnosis. Favourable prognosis is dependent on the early initiation of HF medications. Although full recovery occurs in around half of cases, left ventricular systolic dysfunction persists in a significant proportion of patients with PPCM and the risk of recurrence in subsequent pregnancies is high. The pathophysiology of PPCM is under intense research. We present four patients with PPCM and a review of the literature. Owing to the diagnostic challenge of PPCM and decompensated HF in pregnant mothers and its high mortality rate without treatment, prompt investigation and referral are key to improving maternal survival.